Beyond Tenure: A Quasi-Experimental Causal Analysis of Community Forest Management on Peatland Biodiversity, Carbon Stocks, and Management Efficacy in Sumatra - Jasmila Tanjung; Sarah Armalia; Jovanka Andina; Caelin Damayanti (HM Publisher, 2025)
Indonesia's Hutan Desa (HD, Village Forest) program is a cornerstone of global social forestry, yet its causal ecological impacts remain contested. Rigorous, counterfactual-based evidence is urgently needed to validate this policy intervention, particularly in globally critical peat-swamp landscapes. This study employed a quasi-experimental design, using Propensity Score Matching (PSM) to construct a statistically balanced sample of 40 HD (treatment) and 40 non-HD (control) village units in Sumatran peatlands. We analyzed data from 400 1-hectare permanent sample plots (5 plots nested per village). We assessed floral diversity (Shannon-Wiener Index, H'), faunal presence, and ecosystem carbon stocks (Above-Ground, AGB; Soil Organic Carbon, SOC). Causal impacts were quantified using Linear Mixed-Effects Models (LMMs) to account for the nested data structure. We further analyzed the